2022
DOI: 10.1136/jitc-2021-003532
|View full text |Cite|
|
Sign up to set email alerts
|

Soluble CD137 as a dynamic biomarker to monitor agonist CD137 immunotherapies

Abstract: BackgroundOn the basis of efficacy in mouse tumor models, multiple CD137 (4-1BB) agonist agents are being preclinically and clinically developed. The costimulatory molecule CD137 is inducibly expressed as a transmembrane or as a soluble protein (sCD137). Moreover, the CD137 cytoplasmic signaling domain is a key part in approved chimeric antigen receptors (CARs). Reliable pharmacodynamic biomarkers for CD137 ligation and costimulation of T cells will facilitate clinical development of CD137 agonists in the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…eCFP/NF-κB reporter Jurkat cells were transduced with lentivirus encoding for an anti-mesothelin BBz CAR, provided by S. Guedán (Hospital Clinic, Barcelona, Spain) and C. June (University of Pennsylvania, Philadelphia, PA, USA) ( 81 ). After 6 hours, CAR expression was confirmed by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…eCFP/NF-κB reporter Jurkat cells were transduced with lentivirus encoding for an anti-mesothelin BBz CAR, provided by S. Guedán (Hospital Clinic, Barcelona, Spain) and C. June (University of Pennsylvania, Philadelphia, PA, USA) ( 81 ). After 6 hours, CAR expression was confirmed by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, lymphocyte activation correlates with an increase in sCD137 levels approximately 3 days afterward, hinting at the potential role of sCD137 in dampening T cell activation and CD137-dependent costimulatory signaling pathways [14]. Given that plasma sCD137 signifies prior CD137 activation [34], its elevated levels in SIRS/sepsis patients implies an early activation of CD137 signaling during severe illness.…”
Section: Discussionmentioning
confidence: 96%
“… 32 In a different context, Glez-Vaz et al reported that anti-CD137 agonists led to an sCD137 increase in mice bearing syngeneic tumors. 33 Taken together, serum levels of IL-27 and sCD137 could be synergistically elevated by activating the CD137 signaling pathway to trigger an inflammatory response in liver cancer. This mechanism may be the reason why IL-27 and sCD137 had a positive correlation in our study.…”
Section: Discussionmentioning
confidence: 99%